A highly effective approach to cofactor regeneration and subsequent membrane separation of bioconversion products: Kinetic parameters and effect of process conditions. (February 2020) - Bachosz, Karolina; Zdarta, Jakub; Marczak, Łukasz; Błażewicz, Jacek; Jesionowski, Teofil
Abstract: Bioconversion of monosaccharides is a process which can be used to obtain value-added compounds such as xylonic acid. In this study, we demonstrate enzymatic conversion of xylose with simultaneous cofactor regeneration using co-immobilized xylose dehydrogenase and alcohol dehydrogenase. The research is focused on the effect of process parameters, the buffer solutions used and inhibitors on the enzyme activity, as well as demonstrating the effective separation of substrates and products. In addition, kinetic parameters were determined and the K m and V max values after immobilization were found to be respectively 15–20% higher and 10% lower than the values for free proteins. Moreover, the highest NADH residual was recorded when TAPSO buffer was used, and it was shown that phenolic monomers do not significantly alter the bioconversion efficiency. Finally, the highest retention of xylonic acid, using membrane separation, was found to be about 90% at pH 9. Graphical abstract: Unlabelled Image Highlights: The proposed biosystem enables efficient xylose conversion and cofactor regeneration. The kinetic parameters confirmed that this system can be used in biomass conversion. TAPSO buffer is the best environment for high efficiency of cofactor regeneration. Co-immobilization of XDH and ADH improved their stability against inhibitors. Membrane technology as an efficient method for separation of xylonic acid.